2019
DOI: 10.1136/jclinpath-2019-205820
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning algorithms for the detection of spurious white blood cell differentials due to erythrocyte lysis resistance

Abstract: AimsRed blood cell (RBC) lysis resistance interferes with white blood cell (WBC) count and differential; still, its detection relies on the identification of an abnormal scattergram, and this is not clearly adverted by specific flags in the Beckman-Coulter DXH-800. The aims were to analyse precisely the effect of RBC lysis resistance interference in WBC counts, differentials and cell population data (CPD) and then to design, develop and implement a novel diagnostic ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…25 The ultimate goal of the lymphocytosis diagnosis approach is to classify the encounter as benign or neoplastic 2,3,5 ; moreover, we included the spurious category, as it was previously reported that erythrocyte-lysis resistance phenomenon may lead to spurious lymphocytosis when using the DxH 800 analyzer. 17 The model validation revealed global, weighted, validation accuracy for the different diagnostic categories, corresponding to 95.8%, and a 91.0% accuracy in the POC. An accuracy above 90% is remarkable in view of the difficult diagnostic problem achieving, or even outperforming, the human-level performance reported by the EQA schemes.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…25 The ultimate goal of the lymphocytosis diagnosis approach is to classify the encounter as benign or neoplastic 2,3,5 ; moreover, we included the spurious category, as it was previously reported that erythrocyte-lysis resistance phenomenon may lead to spurious lymphocytosis when using the DxH 800 analyzer. 17 The model validation revealed global, weighted, validation accuracy for the different diagnostic categories, corresponding to 95.8%, and a 91.0% accuracy in the POC. An accuracy above 90% is remarkable in view of the difficult diagnostic problem achieving, or even outperforming, the human-level performance reported by the EQA schemes.…”
Section: Discussionmentioning
confidence: 94%
“…12 Machine learning (ML) is a tool that uses information from different sources, finding patterns from training data and allowing predictions to be made with classification purposes. 13,14 Building on prior experiences using ML and CPD to address lymphocytosis diagnosis in benign or neoplastic categories, 15,16 excluding spurious lymphocytosis, 17 The goal was to develop a CPD-based ML model as an aid to the lymphocytosis diagnosis approach and evaluate its feasibility, standardization, and benefit-cost ratio. Moreover, as it is expected that this ML model would be integrated into the general routine workflow, a proof of concept (POC) was also designed to evaluate its daily-basis performance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Blood was collected from mice by using a retro-orbital puncture. The numbers of Red blood cell (RBC), white blood cell (WBC), and Platelet (PLT) in the blood were detected and analyzed by an automatic cellular analyzers (DXH-800, Beckman Coulter) ( Bigorra et al., 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Bigorra et al [ 34 ] investigated the use of ML to build a model that can use cell population data parameters to improve the detection of liver disease and anemia in samples with abnormal scattergrams. Multiple algorithms have been used, including random forests, naive Bayes classifiers, k -NN, neural networks, and SVM.…”
Section: And DL In the Diagnosis Of Hematological Diseasesmentioning
confidence: 99%